As chaves do paraíso: profecia e alegoria na obra de Padre Antônio Vieira - Martini, Marcus de (2011)
The prophetical writings of Father Antonio Vieira (1608 1697) had an ambiguous reception by the critics. Initially, as one can see in João Lúcio de Azevedo (1855 1933), among others, it was considered a kind of misstep , something curious or extravagant, only understandable in face of the Iberian historical context of the Sixteenth and Seventeenth centuries. More recently, mainly with Alcir Pécora s critical book (1994) and with the works by João Adolfo Hansen, Luso-brazilian texts from the Sixteenth and Seventeenth centuries started to be seen under a new prism, which aims at finding an archaeology of composition instead of just applying outdated analytical categories. Thus, this dissertation aimed at researching Vieira s prophetical writings, specially the texts written during his process in the Holly Office, based on political-theological-rhetorical concepts common to Vieira s time. One searched to analyze the concept of prophecy and the argumentative developments of its use regarding Vieira s interpretative strategies to the defense of the Trovas of the Portuguese cobbler Bandarra (1500 1556) in the Inquisition and to the conception of Vieira s idea of the Fifth Empire , or the Kingdom of Christ on Earth . This analysis stemmed from a historical contextualization and from the comparative reading of the corpus composed by Vieira s prophetical works, read under theological and rhetorical concepts. To this reading, the notions of prophecy and vision served as a background to the study of allegory . This analysis showed the relevance of these concepts for a better comprehension of Vieira s exegesis, in which the use of allegory reveals the fashioning of a prophecy interpreter as a real prophet, responsible for showing the presence of the Divine Providence among mankind and also for participating as an instrument to the arrival of the future Kingdom of Christ.